Smart safety gloves / Mohamad Mirza Harith Suhaimi and Mohamad Hamdan Othman - Suhaimi, Mohamad Mirza Harith; Othman, Mohamad Hamdan (2023)
The construction industry in Malaysia has risen to become the fastest growing industry in Malaysia. As a revolution in the construction industry, the demand for safety gloves has also increased. A pair of safety gloves is recognised as personal protective equipment (PPE) for hand protection on construction sites. The Occupational Safety and Health Act (OSHA) requires employers to ensure that their employees wear safety gloves when working in environments where there is a possibility of hand injury. In the construction industry, safety gloves are very important because the workers are exposed to hazards at work. Based on previous studies, there are several issues regarding the safety and comfort levels of workers when it comes to safety gloves in construction workspaces. This research focuses on safety gloves as a safety tool at construction sites. The findings showed that the existing safety gloves do not provide a high level of protection to workers at the construction site. If the safety gloves do not provide enough protection to the construction workers, it can have adverse effects such as permanent disability, injury, and so on.